PENYULUHAN SI BILLY (AKSI BEBAS BULLY) SEBAGAI UPAYA PENCEGAHAN KASUS BULLYING - Hilmadilla Praja, Dena; Liviyani, Leni; Trysiani, Nabila Ayu; Maulida, Siti Zakiyah; Suganda, Silviani; Laksono, Bayu Adi (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Bullying is a form of violence that occurs among teenagers, especially in the school environment. Bullying is an act of violence carried out by a person or group of people who have power, which is carried out verbally, physically or psychologically. The impact that occurs on victims of bullying is that they experience various mental and physical health problems. The Si Billy Program (bullying-free action) is one of the efforts to overcome bullying, this program is an innovation that we have carried out on existing programs at the Ciamis Regency Population Control, Family Planning, Women's Empowerment and Child Protection (DP2KBP3A) Service. namely the population alert school (SSK) in the field of population control (DALDUK). Service activities were carried out in 2 schools in Ciamis Regency, namely SMPN 1 Cisaga and SMPN 1 Cijeungjing. This activity aims to provide education to teenagers about the dangers of bullying and increase awareness of mutual tolerance towards differences, in order to support the creation of a positive environment. The way to carry out this activity is through counseling designed in the form of material presentation and questions and answers. Activities are carried out at different times in each school. Through this activity, teenagers gain an understanding of bullying, have knowledge about what bullying is, types of bullying, causes, impacts, handling efforts and bullying mechanisms.